Performance Characterictics Of Single Stage Micro Gas Turbine (Mgt) Running On Liquid Biofuels - Mafazi, Muhammad Asri Asyraaf (Universiti Sains Malaysia, 2021)
Liquid biofuels are getting expanding consideration as a group of renewable fuels with potential to assist with mitigate climate change, further develop energy security, and rejuvenate agricultural economies. Liquid biofuels can be an environmentally benign energy source for fixed applications like gas turbines. Vegetable oils are very encouraging alternative fuels of diesel fossil fuel. Palm oil is one of those alternative fuels where its chemical and physical properties are not far from diesel. Micro gas turbines (MGT) are compact scale autonomous and solid dependable circulated generation systems that provide possible energy saving and lowering the emissions of carbon monoxide (CO). They are depended upon to assume an essential part in upcoming supplies of energy for far away areas with or without associations of grid. In this project, a design and development of a combustion chamber for MGT was performed by SOLIDWORKS and CFD simulation (ANSYS-Fluent) software to optimize the geometry of combustion chamber for low-grade liquid biofuels and to characterize the evaporation and combustion performance of palm oil for the different combustion chamber design configurations. Distinctive chamber designs were utilized to simulate with species transport to decide the optimum design of the chamber. The best optimum combustion chamber design is combustion chamber with revolve recycle tube with center air inlet from top. The reason for choosing this chamber since it has the lowest CO emission and NOx emission at the outlet with 0.045128 and 3.37E-05, respectively and it has the lowest result in terms of temperature, CO emission and NOx emission at the contours with the value of 2560 K, 0.182 and 0.000323, respectively.